ØªØ·Ø±ÙØ± Ø§ÙÙØ°ÙÙØ±Ø© ÙØ´Ø±Ø ÙØ¸Ù Ø§ÙØ¹ÙØ±ÙØ·Ù Ø¨Ø®Ø±ÙØ·Ø© Ø§ÙÙÙØ§ÙÙÙ - mufid, miftahul (AN-NAS, 2017)
Qowaid have an important role in the understanding of the Arabic language, As for the difficulties faced The female students MTs Mambaus Sholihin is difficult to understand the book Nahwu (Syarah Nadhom Imrithy) The book requires a development in form, so it fits with the desire of the students of today. The development eg by using electronic media are being developed today. therefore, researchers developed the book so that the students can understand them well. His research is teaching materials developed with the following steps (1) preparing the materials (2) preparing media for development (3) the implementation of the development (4) Evaluation of the questionnaire Validator for advice and criticism and test students to get the data about the effectiveness of the implementation of the Product. from the results of the questionnaire validator that the data obtained Handout to Sarah Nadhom Imrithy with Mindmapping can be used in the learning process with minor repairs. And from the results of data analysis tests showed that the handouts for Sarah Nadhom Imrithy with Mindmapping Effective to improve the material kefahaman nahwu. And from the student questionnaire responses obtained from the data 89% indicate the criteria nice